Comparison of survival rates in four inbred mouse strains under different housing conditions: effects of environmental enrichment - Kajitani, Naoyo; Matsuo, Hiroyuki; Kawakami, Kohei; Matsumoto, Ken-ichi; Yamada, Takaya (EXPERIMENTAL ANIMALS, 2022)
Housing conditions can affect the well-being of laboratory animals and thereby affect the outcomes of experiments. The appropriate environment is essential for the expression of natural behavior in animals. Here, we compared survival rates in four inbred mouse strains maintained under three different environmental conditions. Three mouse strains (C57BL/6J, C3H/HeN, and DBA/2J) housed under environmental enrichment (EE) conditions showed improved survival; however, EE did not alter the survival rate of the fourth strain, BALB/c. None of the strains showed significant differences in body weights or plasma corticosterone levels in the three environmental conditions. For BALB/c mice, the rates of debility were higher in the EE group. Interestingly, for C57BL/6J and C3H/HeN mice, the incidence of animals with alopecia was significantly lower in the EE groups than in the control group. It is possible that the enriched environment provided greater opportunities for sheltering in a secure location in which to avoid interactions with other mice. The cloth mat flooring used for the EE group was bitten and chewed by the mice. Our findings suggest that depending on the mouse strains different responses to EE are caused with regard to health and survival rates. The results of this study provide basic data for further studies on EE.